EFFICACY OF EDUCATIONAL PROGRAM ON MEDICAL PRACTITIONER'S PERCEPTION ON RADIOLOGICAL EXAMINATION - MR. SURESH SUKUMAR,; DR. RAJAGOPAL K. V,; DR. SABU K M,; MRS. KR. BANUMATHE, (International Journal of Pharma and Bio Sciences, 2016)
To measure the efficacy of educational programs and compare the perception among intervention and control group. The research design comprises a quasi-experimental design. Initial data collection was undertaken at the baseline (Pretest) prior to interventions, and then again following that intervention (Post-test).The study employs demonstrated equivalent populations prescribing the radiology examination at the two hospitals (experimental and control). The result clearly highlights the lack of participants’ perception on essential biological facts of radiation and radiology equipment’s after intervention in both intervention and control groups. The items included both the domains of the tool of ionizing and non-ionizing imaging modality used in the medical imaging with respect to the radiation dose involved in the imaging procedure. It also highlights the perception of biological radiosensitive tissues, the Intensity of biological effects of radiation and the dose range involved in the examination. The medical practitioner’s shows increase perception in the intervention group on the radiological examination as compared to the control group.